2021
DOI: 10.3389/fnins.2021.796437
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Effective Connectivity in the Default Mode Network of Autism After an Intervention

Abstract: Neuroimaging has revealed numerous atypical functional connectivity of default mode network (DMN) dedicated to social communications (SC) in autism spectrum disorder (ASD), yet their nature and directionality remain unclear. Here, preschoolers with autism received physical intervention from a 12-week mini-basketball training program (12W-MBTP). Therefore, the directionality and nature of regional interactions within the DMN after the intervention are evaluated while assessing the impact of an intervention on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For example, Hogeveen et al examined cross-network connectivity between these three networks and suggested that the SN-DMN connection is associated with greater internalization in ASD (Hogeveen et al, 2018). Yu et al found that changes of EC in the DMN were significantly associated with the social responsiveness scores in ASD (Yu et al, 2021). Olson et al showed that relationships between FC and autism symptoms in ASD vary by sex (Olson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hogeveen et al examined cross-network connectivity between these three networks and suggested that the SN-DMN connection is associated with greater internalization in ASD (Hogeveen et al, 2018). Yu et al found that changes of EC in the DMN were significantly associated with the social responsiveness scores in ASD (Yu et al, 2021). Olson et al showed that relationships between FC and autism symptoms in ASD vary by sex (Olson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, metabolic modulation may progressively lead to structural and functional changes in the cranial nervous system. In this regard, a Chinese research team has used brain imaging techniques to find changes in white matter fiber connectivity with exercise intervention ( 16 ) and changes in functional brain connectivity such as the default mode network (DNM) and executive control network (ECN) during resting state ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%